Influence mechanisms of fly ash in magnesium ammonium phosphate cement. (3rd January 2022) - Liu, Yuantao; Chen, Bing; Dong, Biqin; Wang, Yanshuai; Xing, Feng
Highlights: The chemical effect of FA in MAPC is lower than GP and GGBS. FA mainly plays a physical ball-bearing effect for workability improvement. FA enhances the later-stage strength and water resistance by the micro-aggregate effect. FA promotes the generation and crystallization of hydrates and modifies the microstructure. Abstract: This research systematically investigated the effects of fly ash (FA) in magnesium ammonium phosphate cement (MAPC) on the fluidity, setting time, compressive strength, and water resistance. The microscopic measurements and analyses, e.g., X-ray diffraction (XRD), thermogravimetric analysis (TGA), Fourier transform infrared spectrometer (FTIR), mercury intrusion porosimetry (MIP), and scanning electron microscopy (SEM) equipped with energy dispersive spectrometer (EDS) were conducted to elaborate the influence mechanisms of FA in MAPC. The reaction potential test results indicate that the chemical effect of FA in the MAPC system is lower than glass powder (GP) and ground granulated blast furnace slag (GGBS). FA mainly plays a physical ball-bearing effect during the initial hardening period of the fresh MAPC mortar for fluidity improvement and setting time prolongation. Besides, FA behaves a micro-aggregate effect during the hardened stage, where FA particles can compact the MAPC. Another effect is that the FA particle acts as the crystal nucleus in MAPC to promote the generation/crystallization of hydration products, e.g., the transformation from the hydrous magnesium ammonium phosphate to crystalline struvite constantly. Such promotion enables enhancing the later-stage mechanical properties (7d, 28d) and water resistance of FA-MAPC. Typically, the group F30 (30% FA) had the fluidity, initial setting time, and compressive strength value of 18 min, 286 mm, and 81.0 MPa, respectively, which exhibited a high property as a repairing material. The current results are helpful to understand the influence mechanisms of FA in MAPC.